(untitled) (Communications in Computational Physics, 2022)
We propose Poisson integrators for the numerical integration of separable Poisson systems. We analyze three situations in which Poisson systems are separated in three ways and Poisson integrators can be constructed by using the splitting method. Numerical results show that the Poisson integrators outperform the higher order non-Poisson integrators in terms of long-term energy conservation and computational cost. The Poisson integrators are also shown to be more efficient than the canonicalized sympletic methods of the same order.